2007
DOI: 10.1124/jpet.107.121749
|View full text |Cite
|
Sign up to set email alerts
|

Low Sensitivity of the Positron Emission Tomography Ligand [11C]Diprenorphine to Agonist Opiates

Abstract: Previously, we reported minimal opioid receptor occupancy following a clinical dose of the -opioid agonist, methadone, measured in vivo using positron emission tomography (PET) with [11 C]diprenorphine and subsequently used rats to obtain experimental data in support of a high receptor reserve hypothesis (Melichar et al., 2005). Here, we report on further preclinical studies investigating opioid receptor occupancy with oxycodone (-and -receptor agonist), morphine (-receptor agonist), and buprenorphine (partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…The consequence of inhibiting P-gp on the 11 Cdiprenorphine distribution volume remains to be evaluated in vivo. Hume et al suggested that this could be a factor influencing variations in the brain uptake of 11 C-diprenorphine (41). (R,S)-PK11195 has been found to be a potent inhibitor of the human P-gp and BCRP on multidrug resistant cells in vitro (42).…”
Section: Discussionmentioning
confidence: 99%
“…The consequence of inhibiting P-gp on the 11 Cdiprenorphine distribution volume remains to be evaluated in vivo. Hume et al suggested that this could be a factor influencing variations in the brain uptake of 11 C-diprenorphine (41). (R,S)-PK11195 has been found to be a potent inhibitor of the human P-gp and BCRP on multidrug resistant cells in vitro (42).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments [30] have shown that mu-receptor binding of agonist like morphine or potentially heroin, are significantly reduced with buprenorphine. Although the outcome for short-term therapy is beneficial, in the long term, administration of buprenorphine will result in an attenuation of mu receptor occupancy of the natural opioid enkephalin and will eventually, like naloxone, result in reduced release of DA at the accumbens brain region [3134].…”
Section: Potential Anti-reward Properties Of Long Term Opioid Replacementioning
confidence: 99%
“…Previous studies suggest that because of a proposed high-efficacy and low-occupancy profile of opioid receptor agonists such as methadone, [ 11 C]diprenorphine is not a suitable radioligand for determination of dose-occupancy relationships in vivo. 19,20 Moreover, the ability of methadone to reduce [ 11 C]carfentanil binding has also not been assessed. The occupancy model may not sufficiently describe the changes in binding observed during in vivo competition imaging paradigms; 21 therefore, the cellular processes underpinning these changes warrant further investigation.…”
Section: Introductionmentioning
confidence: 99%